A comprehensive review of state-of-the-art concentrating solar power (CSP) technologies: Current status and research trends. (August 2018) - Islam, Md Tasbirul; Huda, Nazmul; Abdullah, A.B.; Saidur, R.
Abstract: Concentrating solar power (CSP) has received significant attention among researchers, power-producing companies and state policymakers for its bulk electricity generation capability, overcoming the intermittency of solar resources. The parabolic trough collector (PTC) and solar power tower (SPT) are the two dominant CSP systems that are either operational or in the construction stage. The USA and Spain are global leaders in CSP electricity generation, whereas developing countries such as China and India are emerging by aggressive investment. Each year, hundreds of articles have been published on CSP. However, there is a need to observe the overall research development of this field which is missing in the current body of literature. To bridge this gap, this study 1) provides a most up-to-date overview of the CSP technologies implemented across the globe, 2) reviews previously published review articles on this issue to highlight major findings and 3) analyzes future research trends in the CSP research. Text mining approach is utilized to analyze and visualize the scientific landscape of the research. Thermal energy storage, solar collector and policy-level analysis are found as core topics of discussion in the previous studies. With a holistic analysis, it is found that direct steam generation (DSG) is a promising innovation which is reviewed in this study. This paper provides a comprehensive outlook on the CSP technologies and its research which offers practical help to the future researchers who start to research on this topic. Highlights: Provides a most up-to-date overview of the CSP technologies. Reviews previously published review articles on this issue to highlight major findings. Analyzes future research trends in the CSP research using text-mining approach. Summarizes direct steam generation (DSG)-related research topic. Offers practical help to future researchers.